Probing surface states in C60 decorated ZnO microwires: detailed photoluminescence and cathodoluminescence investigations - Rodrigues, Joana (2019)
ZnO microwires synthesised by the flame transport method and decorated with C60 clusters were studied in detail by photoluminescence (PL) and cathodoluminescence (CL) techniques. The optical investigations suggest that the enhanced near band edge recombination observed in the ZnO/C60 composites is attributed to the reduction of the ZnO band tail states in the presence of C60. Well-resolved free and bound excitons recombination, as well as 3.31 eV emission, are observed with increasing amount of C60 flooding when compared with the ZnO reference sample. Moreover, a shift of the broad visible emission to lower energies occurs with increasing C60 content. In fact, this band was found to be composed by two optical centres peaked in the green and orange/red spectral regions, presenting different lifetimes. The orange/red band exhibits faster lifetime decay, in addition to a more pronounced shift to lower energies, while the peak position of the green emission only shows a slight change. The overall redshift of the broad visible band is further enhanced by the change in the relative intensity of the mentioned optical centres, depending on the excitation intensity and on the C60 flooding. These results suggest the possibility of controlling/tuning the visible emission outcome by increasing the C60 amount on the ZnO surface due to the surface states present in the semiconductor. An adequate control of such phenomena may have quite beneficial implications when sensing applications are envisaged.